Selected measures as predictors of success in advanced algebra and physics at the Magsaysay High School - Pascua, Leonarda B. 1928 (s.n.], 1967)
The objective of the study is to describe selected measures like Philippine Self-Administering Test of Mental Ability, the Bureau of Public Schools Mathematical Ability Test, and the Orleans Algebra Prognosis Test, and the final grade in elementary algebra as predictors of success in two high school subjects, Advanced Algebra and Physics. This also determines the combinations of measures which will result in optimum regression estimates of achievement in Advanced Algebra and Physics . Results of the study may provide tools that will enable counselors to effectively assist students in making appropriate curricular choices and to provide guidelines in planning the instructional program.